The Effects of the Face Mask on the Skin Underneath: A Prospective Survey During the COVID-19 Pandemic - Leelawadee Techasatian; Sirirus Lebsing; Rattapon Uppala; Wilairat Thaowandee; Jitjira Chaiyarit; Chanyut Supakunpinyo; Sunee Panombualert; Dara Mairiang; Suchaorn Saengnipanthkul; Khunton Wichajarn; Pakaphan Kiatchoosakun; Pope Kosalaraksa (SAGE Publishing, 2020)
Purpose: The study aimed to explore the prevalence and possible risk factors to prevent the face mask related adverse skin reactions during the ongoing COVID-19 after a recommendation of face mask wearing for public use in Thailand. Results: The prevalence of face mask related adverse skin reactions was 454 cases (54.5%), of which acne was the most frequent (399; 39.9%), followed by rashes on the face (154; 18.4%), and itch symptoms (130; 15.6%). Wearing a surgical mask showed a higher risk of adverse skin reaction compared to a cloth mask, OR (95% CI) = 1.54 (1.16-2.06). A duration of face mask wearing of more than 4 hours/day and the reuse of face masks increased the risk of adverse skin reactions compared to changing the mask every day, adjusted OR(95% CI) = 1.96 (1.29-2.98), and 1.5 (1.11-2.02). Conclusion: Suggestions were made for wearing a cloth mask in non-health care workers (HCW) to decrease the risk of face mask related adverse skin reactions. This suggestion could potentially help in decreasing the demand of surgical masks which should be reserved for the HCW population during the ongoing COVID-19 pandemic.